(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: retroperitoneal laparoscopic surgery for Treating ureteropelvic junction obstruction (UPJO) at Transport Hospital from 4/2024 -4/2025. Results: In 4 patients ureteropelvic junction obstruction, cause included: 2 cases inferior renal artery crosses ureter, 1 case incomplete duplicated ureter, 1 case high insertion of the ureter. 4 case was be retroperitoneal laparoscopic surgery. 3 patients underwent dismembered pyeloplasty, 1 patients underwent non-plastic surgery. Operation time from 105-120 minutes. Duration of treatment after surgery was 7 days. No any case has surgical complication. After 6 months, 1 case was checked CT- Scanner. Flowing from kidney to ureter is nomal. Conclusions: Retroperitoneal laparoscopic surgery to treat ureteropelvic junction obstruction has been safe, and has a high success rate, giving the same result as open surgery.